Evaluation of vascular endothelial growth factor gene and protein expression in canine metastatic mammary carcinomas - Raposo-Ferreira, Talita M. M. [UNESP]; Salvador, Rosana C. L. [UNESP]; Terra, Erika M. [UNESP]; Ferreira, Juarez H. [UNESP]; Vechetti-Junior, Ivan Jose [UNESP]; Tinucci-Costa, Mirela [UNESP]; Rogatto, Silvia R. [UNESP]; Laufer-Amorim, Renee [UNESP] (Wiley-Blackwell, 2016)
Vascular endothelial growth factor (VEGF) is a potent angiogenic factor that could be associated with the induction of endothelial cell proliferation and metastasis. In this study, we evaluated VEGF gene and protein expression in canine mammary tumors (CMT), including metastatic carcinomas, to determine if there is an influence of this marker in the malignant processes and aggressiveness of CMT. We also compared VEGF protein levels with clinicopathological features. The VEGF gene and protein expression levels were evaluated by reverse transcription-quantitative polymerase chain reaction and immunohistochemistry, respectively, in normal mammary gland samples, benign mammary tumors, nonmetastatic mammary carcinomas, and metastatic mammary carcinomas. High VEGF gene and protein levels were associated with malignant tumors compared with normal mammary glands (p = 0.0089 and p < 0.0001, respectively). Benign tumors showed an increased VEGF protein expression compared with normal samples (p = 0.0467). No significant differences in VEGF gene or protein levels were detected between benign and malignant tumors or between nonmetastatic and metastatic carcinomas, suggesting an absence in the correlation of VEGF with malignant processes and aggressiveness of CMT. No correlation of VEGF expression with clinical and histopathological parameters was observed, suggesting that VEGF could be important in the beginning of the mammary gland carcinogenic process and could be related to survival time.
Keywords: dog; mammary gland; metastasis; tumor; VEGF